CULTURAL SPECIFICITY IN EXPRESSIONS OF REPROACH: A CROSS-CULTURAL PRAGMATIC ANALYSIS - Mukhtorova, Mokhlaroyim (QO‘QON UNIVERSITETI XABARNOMASI, 2024)
This study examines the cultural specificity in expressions of reproach, emphasizing the diverse language and pragmatic tactics employed by different cultures to convey disapproval or criticism. Reproach, as a communicative act, is profoundly shaped by cultural norms, beliefs, and communication methods, which can differ markedly throughout countries. This study integrates discourse analysis and cross-cultural pragmatics to examine the articulation of rebuke in both direct and indirect forms across various cultural contexts. The results demonstrate that although reproach is universally acknowledged as a face-threatening act, its manifestation varies based on cultural perspectives regarding authority, hierarchy, and social cohesion. This study enhances the comprehension of cultural specificity’s impact on interpersonal communication, especially on the expressing of rebuke, and provides insights into intercultural communication practices.